Meeting Yahweh's requirements - a proposed reading of Micah 6:1-8 - Wessels, Willie (Old Testament essays, 2002)
The book of Micah has a complex compositional history. There are quite a number of theories suggesting a solution to the problem. Many of these theories are real possibilities, but it seems the final word on the issue will never be spoken. The real challenge in the light of these realities is to propose possible readings of the collection of texts ascribed to Micah as we now have. As the focus of this article is on Micah 6:1-8, the question is how to read it as part of the collection of Micah texts. From research it seems that it is possible to argue that the first five chapters have a great deal to do with leadership matters and abuse of power. To a large extent the common people are the victims of the raging conflict in leadership. However, it seems that in chapters six and seven the common people are more in focus. These chapters with their liturgical overtones encourage the common people to conduct their lives in a responsible manner. From a holistic perspective of the book as a collection, it therefore seems plausible to read chapters six and seven from a vantage point of the common people. In this sense the book addresses not only the leaders of society, but the people of society as a whole, leaders and common people.